The Name Day as a Part of Medieval Historiographical Narrative - Anna F. Litvina; Fjodor B. Uspenskij (Slovene, 2015)
The article investigates the ways in which the celebration of the name day (imeniny) of Russian princes or their entourages was presented in the Russian chronicles. The custom of celebrating the name day was firmly rooted in the Russian princely environment. For a chronicle narrative, the very rootedness of this custom and the number of its associated actions plays an important role—it is this rootedness that makes stories told in the chronicles quite opaque to the modern reader. A prince’s Christian name and the day of his patron saint were considered to be important background knowledge for the audience of the medieval compiler. There were, apparently, clear ideas about appropriate behavior for prince or a person from his environment on his name day or on the eve of this day but, on the other hand, such assumptions explain why this kind of “normal” behavior rarely forms the subject of special reflection in the chronicles. It is not only a description of the celebration itself that might be very informative, whether it be a church service, a ceremonial feast with various relatives, or an exchange of gifts, but also the description of acts and deeds that were undertaken specifically on a prince’s name day. Therefore, particular attention is given here to stories about undue or inappropriate behavior on this special day. The paper deals with the function and nature of such episodes in the broader context of historiographical narrative.